2017
DOI: 10.1103/physrevx.7.031040
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Enhancement of Coherent Photon Generation from a Nitrogen-Vacancy Center in Ultrapure Diamond

Abstract: The nitrogen-vacancy (NV) center in diamond has an optically addressable, highly coherent spin. However, an NV center even in high quality single-crystalline material is a very poor source of single photons: extraction out of the high-index diamond is inefficient, the emission of coherent photons represents just a few per cent of the total emission, and the decay time is large. In principle, all three problems can be addressed with a resonant microcavity. In practice, it has proved difficult to implement this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
222
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(228 citation statements)
references
References 52 publications
4
222
2
Order By: Relevance
“…The ultimate goal of on‐chip high‐bandwidth quantum state transfer also depends on the quality of microfabricated photonic elements and the advances in diamond‐based device engineering regarding transmission loss reduction and device footprint shrinking. The well‐developed techniques for NV − centers can be immediately transferred to split‐vacancy centers with minimum modifications, such as Fabry–Perot microcavity design, lab‐on‐chip devices, and photonic integrated circuits …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate goal of on‐chip high‐bandwidth quantum state transfer also depends on the quality of microfabricated photonic elements and the advances in diamond‐based device engineering regarding transmission loss reduction and device footprint shrinking. The well‐developed techniques for NV − centers can be immediately transferred to split‐vacancy centers with minimum modifications, such as Fabry–Perot microcavity design, lab‐on‐chip devices, and photonic integrated circuits …”
Section: Discussionmentioning
confidence: 99%
“…The immense interest in the NV − center stems from its outstanding spin properties: the spin‐tagged fluorescence enables optical addressing of ground‐state spin manifold even at room temperature, while the exceptionally long‐lived spin state ( T2=1.8normalms0.33emin 12 C‐enriched sample) allows for an efficient coupling with proximal electronic and nuclear spin in the lattice . Despite the milestone demonstration of spin–photon entanglement on NV − system, this emitter suffers from relatively poor optical properties, including low percentage of zero‐phonon‐line (ZPL) emission with a Debye–Waller factor of 0.03, strong spectral diffusion when located near surfaces, and a relatively long radiative lifetime of 13 ns . These deficiencies fuel the investigation for alternative emitters that combines bright, homogeneous, and coherent optical transitions with the long‐lived quantum memories.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the g does not have to succeed, because incomplete cluster states (with probability of missing entanglement edges below a percolation threshold) are still sufficient for universal quantum computing. NV-centers suffer from low out-coupling efficiencies, though this is conventionally combatted by coupling the center to a cavity [87], which has the added benefit of reducing emission out of the zero-phonon line by the Purcell effect.…”
Section: Experimental Realizationsmentioning
confidence: 99%
“…In 2017, Riedel et al. reported the integration of diamond membranes, detached from the hosting substrate using a micromanipulator, with a chip‐based open‐access microcavity . The authors reported single‐photon emission ( Figure a) and claimed a Purcell factor of ≈30 for the ZPL translated from an overall Purcell factor of 2 (Figure b).…”
Section: Single‐photon Emitters and Nanoparticles In Open‐access Micrmentioning
confidence: 99%